A colorectal cancer diet quality index is inversely associated with colorectal cancer in the Malmö diet and cancer study. Issue 6 (November 2019) - Vulcan, Alexandra; Ericson, Ulrika; Manjer, Jonas; Ohlsson, Bodil
Abstract : The World Cancer Research Fund International has concluded strong evidence for that high intake of dairy products and foods containing dietary fiber and low intake of processed meat are associated with decreased risk of colorectal cancer (CRC). As food items are consumed together, it is important to study dietary patterns. The aim of the present study was to examine the association between an a priori constructed dietary index and incident CRC and between intake of processed meat, fiber, and dairy products and CRC. In the Malmö Diet and Cancer study cohort, 923 cases of CRC were identified, during 502 136 person-years of follow-up. A Colorectal Diet Quality Index (CDQI) was constructed regarding intakes of processed meat, fiber, and dairy products in relation to CRC. Higher index indicated a higher dietary quality. Higher CDQI was associated with lower risk of CRC [hazard ratios (HR): 0.57 for highest compared with lowest quintile; 95% confidence interval (CI): 0.43, 0.75; P <0.001]. Intake of dairy products was inversely associated with risk of CRC [HR for highest vs. lowest quintile was 0.77 (CI: 0.62, 0.96); P = 0.008], as was dietary fiber [HR for highest vs. lowest quintile was 0.77 (CI: 0.61, 0.98); P = 0.043]. High intake of processed meat was associated with CRC [HR for highest vs. lowest quintile was 1.31; CI: 1.05, 1.63; P = 0.012]. High adherence to a predefined CRC-specific diet quality index was inversely associated with the risk of CRC and gave a stronger association with CRC, than when analyzing the components of the CDQI individually.